Obstacles to Improve Human Resources Performance from Employees Point of View - Case Study of the National Electricity and Gas Distribution Corporation, Mila - حيمر, حمود (Milev Journal of Research and Studies, 2019)
In this research, we discussed the subject of obstacles to improve the performance of human resources from its point view- a study of the human resources situation working in the National Electricity and Gas distribution Corporation in Mila. We have divided the research into three axis: The first one to highlight the fact that human resource performance has improved, and the various steps of this process. The second one we devoted to talk about the obstacles that hinder the improvement of the human resources performance, where we divided the obstacles to the source of human resources, and other sources of institutions. The third one includes a field study of the reality of the human resources performance improvement where we found that there are constraints on the jobs and working conditions, especially the incentive system and the lack of means. This requires the intervention